Protection of Gynostemma pentaphyllum Extract on Hemolysis-Induced by Plasmodium berghei Infection in ICR Mice - Borkaew, Preeyanuch; Klubsri2, Chokdee; Somsak, Voravuth (International Journal of Innovative Research in Medical Science, 2016)
Hemolysis is one manifestation of Plasmodium parasite infection and well-known causes of death in severe malaria. The present study was aimed to investigate protective effect of Gynostemma pentaphyllum extract on hemolysis-induced by Plasmodium berghei infection in mice. Aqueous crude extract of G. pentaphyllum leaves was prepared using hot water method. Standard 4-day test was used to evaluate the efficacy of this extract on hemolysis during malaria infection. Groups of ICR mice (5 mice of each) were inoculated with 1x107 parasitized erythrocytes of P. berghei ANKA (PbANKA) by intraperitoneal injection, and subsequently given the extract (100, 1,000, and 3,000 mg/kg) orally by gavage twice a day for 4-consecutive days. The results showed that aqueous crude extract of G. pentaphyllum leaves exhibited significant (p<0.05) dose-dependent protection of hemolysis-induced by PbANKA. The maximum activity was observed at a dose of 3,000 mg/kg extract. Additionally, no any toxicities were found in normal mice treated with this extract. It can be concluded that aqueous crude extract of G. pentaphyllum leaves exerted protective effect on hemolysis-induced by malaria infection.